"In addition to Abdziralovič": characteristic of the life and work of Ihnat Kančeŭski. - Novick Ivan М. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the life and works of Ihnat Kančeŭski, better known under the pseudonym Ignat Abdziralovič - author of the famous essay “Advečnym šlacham” (“By the everlasting way”). Our main conclusion is as follows: the main, almost the only topic Kančeŭski as publicist was cooperation – this topic was riveted on his attention, to it he returned again and again, through the framework of cooperation he analyzed other cultural and social phenomena of the Belarusian life. A significant part of his biography and practical life was associated with cooperation. Therefore, its appearance in the pages of "Advečnym šlacham" is not a coincidence - just these few pages bear the brunt of political philosophy of Kančeŭski, here one should look for the key to understanding of his social outlook.